Prospects for solar water heating within Turkish textile industry - Muneer, T.; Asif, M.; Cimecioglu, Z.; Ozturk, H. K. (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
Turkey is a free market economy that is oriented towards Western markets. It also has strong ambitions to join the European Union and this factor has been beneficial as well taxing with respect to its changing economic situation. In terms of world textile strand production, on a production per capita basis, Turkey occupies the third place in the world. Thus, the economic importance of textile industry for Turkey and its need for consolidation within the world markets is essential. Turkey imports nearly 50% of its energy requirements. The country spends 40-50% of its total export income to import fuel, mainly crude oil and natural gas. The aim of this study is to investigate the possibility of exploitation of solar energy within the Turkish textile industry with particular reference to thermal application and critically examine the present opportunities and barriers. A discussion on the possible adoption of instruments that will help alleviate the barriers is also presented. Results of a detailed life cycle assessment and relevant economics of solar water heater have also been presented. As an addendum the potential for solar water heating within the domestic sector is also briefly discussed. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: solar water heating; sustainable energy systems; energy budget for turkey; renewable energy; PERFORMANCE; RADIATION; Science & Technology - Other Topics; Energy & Fuels